IMPLEMENTASI TWO FACTOR AUTHENTICATION DAN PROTOKOL ZERO KNOWLEDGE PROOF PADA SISTEM LOGIN - Willy Sudiarto Raharjo; Ignatia Dhian E.K. Ratri; Henry Susilo (Maranatha University Press, 2017)
Abstract — This paper describes a login system utilizing Two Factor Authentication and Zero Knowledge Proof using Schnorr NIZK. The proposed system is designed to prevent password leak when being sent over insecure network or when used in an untrusted devices. Zero Knowledge Proof is used for maintaining the confidentiality of the password and Two Factor Authentication is used to secure login process on untrusted devices. The proposed system has been tested and initial results indicates that such system is able to secure the login process without leaking the user’s password. Keywords— Authentication, Security, Two Factor Authentication, Password, Zero Knowledge Proof